Probing the gas-phase structure of charge-tagged intermediates of a proline catalyzed aldol reaction – vibrational spectroscopy distinguishes oxazolidinone from enamine species. Issue 5 (18th January 2019) - Willms, J. Alexander; Vidic, Jandro; Barthelmes, Janosch; Steinmetz, Vincent; Bredow, Thomas; Maître, Philippe; Engeser, Marianne
Abstract : Charge-tagging enables the detection of reaction intermediates which are probed by IRMPD spectroscopy in combination with theory. Abstract : Anl -proline based catalyst with a charged phenyl-pyridium substituent (1 ) was used to analyze intermediates of an organocatalyzed aldol reaction by infrared multi-photon dissociation (IRMPD) mass spectrometry after transfer into the gas phase via electrospray ionization (ESI). IRMPD spectra were interpreted with the aid of density functional theory (DFT) computations. A structurally restricted enamine species was used as a reference molecule for the calculated vibrational frequencies. A close correlation between theory and experiment was found for the energetically most favoured oxazolidinone structures.